Springtail diversity in South Africa - Charlene Janion; Anne Bedos; Jan Bengtsson; Louis Deharveng; Bettine Jansen van Vuuren; Hans Petter Leinaas; Amy Liu; Anna Malmström; David Porco; Steven Chown (South African Journal of Science)
Despite their significance in soil ecosystems and their use for investigations of soil ecosystem functioning and in bioindication elsewhere, springtails (Collembola) have not been well investigated in South Africa. Early recognition of their role in soil systems and sporadic systematic work has essentially characterised knowledge of the southern African fauna for some time. The situation is now changing as a consequence of systematic and ecological work on springtails. To date this research has focused mostly on the Cape Floristic Region and has revealed a much more diverse springtail fauna than previously known (136 identifiable species and an estimated 300 species for the Cape Floristic Region in total), including radiations in genera such as the isotomid Cryptopygus. Quantitative ecological work has shown that alpha diversity can be estimated readily and that the group may be useful for demonstrating land use impacts on soil biodiversity. Moreover, this ecological work has revealed that some disturbed sites, such as those dominated by Galenia africana, may be dominated by invasive springtail species. Investigation of the soil fauna involved in decomposition in Renosterveld and Fynbos has also revealed that biological decomposition has likely been underestimated in these vegetation types, and that the role of fire as the presumed predominant source of nutrient return to the soil may have to be re-examined. Ongoing research on the springtails will provide the information necessary for understanding and conserving soils: one of southern Africa's major natural assets.